2013
DOI: 10.1371/journal.pone.0061170
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle-Dependent Cytoskeletal Modifications in Plasmodium falciparum Infected Erythrocytes

Abstract: Plasmodium falciparum infection of human erythrocytes is known to result in the modification of the host cell cytoskeleton by parasite-coded proteins. However, such modifications and corresponding implications in malaria pathogenesis have not been fully explored. Here, we probed the gradual modification of infected erythrocyte cytoskeleton with advancing stages of infection using atomic force microscopy (AFM). We reported a novel strategy to derive accurate and quantitative information on the knob structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 35 publications
6
92
0
Order By: Relevance
“…In uninfected RBCs, the average spectrin length is 51 ± 9 nm (Fig. 2B), in agreement with previous reports (10,18). In trophozoites and stage III gametocytes, a significant increase in spectrin length was observed (61 ± 14 and 62 ± 8 nm, respectively; P < 0.0001) (Fig.…”
Section: Disruption Of the Gametocyte Microtubule Network Does Notsupporting
confidence: 92%
See 2 more Smart Citations
“…In uninfected RBCs, the average spectrin length is 51 ± 9 nm (Fig. 2B), in agreement with previous reports (10,18). In trophozoites and stage III gametocytes, a significant increase in spectrin length was observed (61 ± 14 and 62 ± 8 nm, respectively; P < 0.0001) (Fig.…”
Section: Disruption Of the Gametocyte Microtubule Network Does Notsupporting
confidence: 92%
“…Atomic force microscopy (AFM) has revealed reorganization and expansion of the spectrin network of the host cell membrane (10,11), while cryo-electron tomography suggests that this reorganization occurs as a result of mining of the actin junctions in order to generate actin filaments that connect parasite-derived organelles known as Maurer's clefts to the knobs (12). A parasiteencoded protein called the Knob-Associated Histidine-Rich Protein (KAHRP) is thought to be a major contributor to RBC rigidification (8,13).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…50 Spectrin tetramers are capable of stretching to 194 nm in length, 51 which would allow for knob intercalation into the cytoskeleton mesh without further modification. It has been reported that the red cell cytoskeleton is gradually dismantled as the intracellular parasite develops, 42,52,53 and it is possible that some cytoskeletal connections are broken during knob formation. However, in this study, which used highly synchronized, mature schizont preparations, no differences in cytoskeletal structure outside of the knobs were observed between uninfected erythrocyte skeletons and those from mature schizonts.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown by atomic force microscopy that the spectrin network is denser and sparser in knobby and nonknobby regions, respectively, and that the spectrin length increases during the replicative cycle (25). Using multiscale modeling, it has been argued that the vertical linking between the knobs and the spectrin network strongly changes the mechanics of the host cell (26).…”
Section: Introductionmentioning
confidence: 99%